Penyuluhan Dan Pelatihan Pelatih Serta Wasit Juri Renang Kategori “D” Di Kabupaten Seluma Tahun 2024 - Apriansyah, Dolly; Putra, Dwingki Marta; Lismana, Oetari (Jurnal Dehasen Untuk Negeri, 2025)
In the Regency, training for coaches and referees for category "D" swimming was held which was attended by various groups such as pupils, students and teachers both within the Province and outside the Province. This activity was carried out in collaboration with Dehasen University Lecturers and Seluma Regency Aquatics. This activity was held on Monday 11 November 2024 and was attended by 66 participants.